Avaliação do curso de Engenharia de Produção baseado no C.D.I.0.: uso do Modelo Toolbox e Diagrama de causa e Efeito - Maciel, Flávio José (2024)
This study aims to evaluate the implementation process of a Pedagogical Project for the Bachelor's Degree in Production Engineering - PPC using the Toolbox model of the Swedish Merut Program and the Ishikawa Cause and Effect Diagram. We sought to understand the implementation process of the institution's current version of the PPC to date. Its objectives are: (i) evaluate how the current Production Engineering course at PUC-SP is executing the project in relation to what was planned in its respective PPC version 2019 (ii) what are the possible factors that influenced its current performance (iii) based on the identification of the main influencing agents, which already provide evidence of potential needs for correction in the execution of the PPC implementation plan, suggest an action plan to improve the results expected by the course. The justification is based on the contribution that the study can make in order to provide the IES with elements to, if necessary after analyzing the results, mitigate deviations in the originally designed planning and in the definition of corrective actions to guarantee the success of the implementation of the PPC in view of the organizational, social and technological scenario of the post-pandemic Industry 4.0 environment. This is an investigative case study, supported by documentary research through an exploratory and descriptive analysis and systematic literature reviews on the main topics related to engineering education. Documentary research was also used through exploratory and descriptive analysis to map projects based on PBL, active methodology and C.D.I.O. Initiative. Finally, an assessment of the current state of the PPC implementation process was carried out through the Toolbox model and the Cause and Effect seeking to identify the main root-causes of possible deviations observed in the investigative phase. At the end of the analysis, the author proposes suggestions for actions that could contribute to the success of the PPC implementation project, which is still in the implementation phase. This study is part of the Postgraduate Program in Intelligence Technology and Digital Design – Pontifical Catholic University of São Paulo under the guidance of Prof. Dr. Daniel Gatti